Stimuli-Responsive Adaptive Nanotoxin to Directly Penetrate the Cellular Membrane by Molecular Folding and Unfolding - Jeong, Youngdo; Jin, Soyeong; Palanikumar, L.; Choi, Huyeon; Shin, Eunhye; Go, Eun Min; Keum, Changjoon; Bang, Seunghwan; Kim, Dongkap; Lee, Seungho; Kim, Minsoo; Kim, Hojun; et al. (American Chemical Society, 2022)
Biological nanomachines, including proteins and nucleic acids whose function is activated by conformational changes, are involved in every biological process, in which their dynamic and responsive behaviors are controlled by supramolecular recognition. The development of artificial nanomachines that mimic the biological functions for potential application as therapeutics is emerging; however, it is still limited to the lower hierarchical level of the molecular components. In this work, we report a synthetic machinery nanostructure in which actuatable molecular components are integrated into a hierarchical nanomaterial in response to external stimuli to regulate biological functions. Two nanometers core-sized gold nanoparticles are covered with ligand layers as actuatable components, whose folding/unfolding motional response to the cellular environment enables the direct penetration of the nanoparticles across the cellular membrane to disrupt intracellular organelles. Furthermore, the pH-responsive conformational movements of the molecular components can induce the apoptosis of cancer cells. This strategy based on the mechanical motion of molecular components on a hierarchical nanocluster would be useful to design biomimetic nanotoxins.